Cervical artery dissection: ethiopathogenesis, symptoms, diagnosis and treatment (literature review) - I. Zagorskienė; A. Paplauskaitė; J. Valaikienė (Neurologijos seminarai)
Cervical artery dissection (CAD) is considered a rare disorder, but among young adults it is a common cause of stroke (causes about 25% of strokes in young adults). So far, the pathophysiology of spontaneous CAD is probably best described as an interaction of genetic and environmental factors. The most frequent symptom of CAD is headache or pain in the face or neck, which might be followed by symptoms of acute cerebral ischaemia. The diagnosis of CAD can be confirmed by various imaging techniques, but it has to be suspected by the clinician first. Acute stroke due to CAD can be treated with thrombolysis, and to prevent stroke (whether primary or secondary) anticoagulants or antiplatelets are used. Unfortunately, no consensus is made for the first-line treatment yet. Endovascular treatment is an alternative option for selected patients. Overall, prognosis of CAD is usually favorable, relapse of stroke is rare, and mortality rate is low.